Nuevos entornos, nuevas demandas, nuevos periodistas - Tuñez López, Miguel; Martínez Solana, Yolanda; Abejón Mendoza, Paloma (Estudios sobre el Mensaje Periodístico, 2010)
The traditional communication model has been overcome. Journalism, as hitherto conceived, modified viewing the role of all actors: the media product, the roles of transmitter and receiver, supports, hearings, formal training ... The engine of change is simultaneously activated sources, media, journalists and audiences, but also is taking a redefinition of productive routines that drive business demand to a profile of journalists specializing in multi media technology. This article reviews the most significant transformations that contemporary journalism has to face, pretending to take a realistic view of the professional stage in sight.
Keywords: Newsmaking; Traditional communication model; Journalism; Multimedia Specialization